2016
DOI: 10.1038/srep23482
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Epithelium Thickness Profile in 614 Normal Chinese Children Aged 7–15 Years Old

Abstract: The purpose of the study is to describe the values and distribution of corneal epithelium thickness (CET) in normal Chinese school-aged children, and to explore associated factors with CET. CET maps were measured by Fourier-domain optical coherence tomography (FD-OCT) in normal Chinese children aged 7 to 15 years old from two randomly selected schools in Shanghai, China. Children with normal intraocular pressure were further examined for cycloplegic autorefraction, corneal curvature radius (CCR) and axial leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 37 publications
(63 reference statements)
1
13
0
Order By: Relevance
“…Thereafter, the scar tissues were formed after corneal edema was repaired, which undoubtedly caused the irregular changes of epithelial thickness in the scarring KC. Since the thickness profiles in some stages of KC had never been investigated based on the AS-OCT, the findings not only supported the previous studies (Li et al, 2012;Ma et al, 2016;Xu et al, 2016;Morishige et al, 2019;Wang et al, 2019;Yang et al, 2020;Toprak et al, 2021), but also provided new evidence for the KC features at different stages. Furthermore, our experimental results with the linear discriminant analysis revealed that the measured thickness indices could be used to differentiate the groups of different KC stages from normal eyes.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Thereafter, the scar tissues were formed after corneal edema was repaired, which undoubtedly caused the irregular changes of epithelial thickness in the scarring KC. Since the thickness profiles in some stages of KC had never been investigated based on the AS-OCT, the findings not only supported the previous studies (Li et al, 2012;Ma et al, 2016;Xu et al, 2016;Morishige et al, 2019;Wang et al, 2019;Yang et al, 2020;Toprak et al, 2021), but also provided new evidence for the KC features at different stages. Furthermore, our experimental results with the linear discriminant analysis revealed that the measured thickness indices could be used to differentiate the groups of different KC stages from normal eyes.…”
Section: Discussionsupporting
confidence: 82%
“…Although the corneal thickness profiles including the epithelial layer have been investigated based on AS-OCT images (Chen et al, 2012;Corre-Perez et al, 2012;Li et al, 2012;Wu et al, 2014;Ma et al, 2016;Xu et al, 2016;Ang et al, 2018;Mathai et al, 2019;Morishige et al, 2019;Ouyang et al, 2019;Santos et al, 2019;Wang et al, 2019;Yang et al, 2020;Toprak et al, 2021), none of them was able to successfully classify the KC into different stages based on the CLEK guidelines (Zadnik et al, 1998). Often, all the KC eyes are considered as a group when compared with normal eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Central corneal thickness (CCT) is also an independent risk factor for glaucoma, and potential factors affecting corneal thickness measurements or their association with IOP measurements have been extensively studied [3,4]. The recent development of topographic mapping using Fourier domain optical coherence tomography (FD-OCT) has enabled the measurement of corneal epithelial thickness (CET) as well as corneal thickness in the clinical routine with various clinical applications [5][6][7]. The corneal epithelium is one of the main structures that undergo degenerative alterations in ocular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The ratio of epithelial to corneal thickness may be a more sensitive criterion for diagnosing dry eye syndrome than simply epithelial thickness as previously suggested. In dry eye syndrome, the thickness of the epithelium increases, but this may be invisible in patients with initially thin epithelium, because even with thickening in patients with a thin cornea, the thickness of the epithelium may not exceed normal values [18].…”
Section: Aim Of the Workmentioning
confidence: 99%